DGUOK‐AS1 promotes cell proliferation in cervical cancer via acting as a ceRNA of miR‐653‐5p. (13th April 2020) - Wu, Nanchang; Song, Honglin; Ren, Yaoyao; Tao, Shan; Li, Shiting
Abstract : Cervical cancer (CC) holds the second highest incidence and is the fourth dominating cause of cancer‐induced death in women. It has been widely accepted that long noncoding RNAs (lncRNAs) are implicated in pathological and physiological activities of CC. However, the research of lncRNAs is still in the initial stage. The biological function of lncRNA deoxyguanosine kinase antisense RNA 1 (DGUOK‐AS1) in human cancers has not been reported yet. We found that DGUOK‐AS1 was aberrantly upregulated in cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC) tissues through TCGA database. Real‐time quantitative polymerase chain reaction (RT‐qPCR) also verified the high expression of DGUOK‐AS1 in CC cell lines. Loss‐of‐function assays indicated that DGUOK‐AS1 silence repressed CC cell growth. In addition, dual‐luciferase reporter and RNA immunoprecipitation (RIP) experiments validated the binding relation between miR‐653‐5p and DGUOK‐AS1 or EMSY. Results of the rescue assays elucidated that EMSY overexpression or miR‐653‐5p downregulation reversed the suppressive function of DGUOK‐AS1 knockdown on cell growth and DNA repair in CC. To sum up, this research highlighted that DGUOK‐AS1 could promote CC cell proliferation via serving as a ceRNA of miR‐653‐5p to release EMSY, which might inspire us to discover novel strategies for CC treatment. Significance of the study: DGUOK‐AS1 knockdown hinders proliferation of CC cells. DGUOK‐AS1 sequesters miR‐653‐5p to elevate EMSY in CC. EMSY is required for DGUOK‐AS1 to induce cell proliferation and repress DNA damage in CC.